DESIGN AND OPERATIONS CHALLENGES OF A SINGLE TOGGLE JAW CRUSHER: A REVIEW (Nigerian Journal of Technology, 2017)
A review on the design and operations challenges of a single toggle jaw crusher is presented. Strength and fracture toughness of the material to be crushed are intrinsic properties that determine the time and energy required to crush the material. Economy of the crushing process is partly dependent on the angle of nip. Productivity of the crusher can be improved upon by increasing the eccentricity of the eccentric shaft, use of reversible jaws, bush bearing and easily adjustable toggle plate. Vibrations and fatigue cracks in the crusher frame will be nipped in the bud through structural analysis at design stage. Determination of the optimal angle of inclination of the toggle plate, development of jaws with varying wear rate along the crushing chamber, and development of comminution energy models that take into cognizance relevant crushing parameters for simulation and optimization of the crushing process are some areas that require close attention.  http://dx.doi.org/10.4314/njt.v36i3.22